A transnational human rights approach to human trafficking: empowering the powerless - Sin, Yun jin (Studies in intercultural human rights, 2018)
Introduction : comprehending human trafficking as a transnational human rights problem -- Analysis of current legal institutional responses : international and regional levels -- Analysis of current legal institutional responses : national level -- Case study 1 : South Korea -- Case study 2 : Taiwan -- International human rights law in the context of human trafficking -- Alternative approaches and remedies : transnational human rights framework